2015
DOI: 10.1002/pssb.201552031
|View full text |Cite
|
Sign up to set email alerts
|

Elastic anisotropy and thermodynamic properties of chromium tetraboride from first‐principles calculations

Abstract: First-principles calculations are performed to investigate the elastic anisotropy, and thermodynamic properties of chromium tetraboride (CrB 4 ) under extreme P-T conditions. The calculated equilibrium lattice and the normalized crystal parameters as a function of pressure are in good agreement with the available experimental and theoretical data. Elastic constants C ij are calculated in the pressure range of 0-50 GPa, and the bulk modulus B, shear modulus G, and Young's modulus E are also obtained according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…The boron sheets are buckled in CrB 4 , FeB 4 , and ReB 4 but flat in MoZrB 4 , TaCrB 4 , and HfNbB 4 . The structures CrB 4 and FeB 4 were examined theoretically in refs and , respectively, where the authors reported elastic modulus values in reasonable agreement with the ones predicted by our ML models: for CrB 4 , the authors reported K = 267 GPa and G = 266 GPa versus our predicted K and G values above; for FeB 4 , the authors reported K = 277 GPa and G = 186 GPa versus our ML-predicted K = 248 GPa and G = 220 GPa. The calculated mechanical properties of TcB 4 were reported by Wang et al for which they reported Voigt moduli K = 291 GPa and G = 88 GPa, whereas our ML models predicted values K = 276 GPa and G = 203 GPa; the G values are not comparable.…”
Section: Resultssupporting
confidence: 61%
“…The boron sheets are buckled in CrB 4 , FeB 4 , and ReB 4 but flat in MoZrB 4 , TaCrB 4 , and HfNbB 4 . The structures CrB 4 and FeB 4 were examined theoretically in refs and , respectively, where the authors reported elastic modulus values in reasonable agreement with the ones predicted by our ML models: for CrB 4 , the authors reported K = 267 GPa and G = 266 GPa versus our predicted K and G values above; for FeB 4 , the authors reported K = 277 GPa and G = 186 GPa versus our ML-predicted K = 248 GPa and G = 220 GPa. The calculated mechanical properties of TcB 4 were reported by Wang et al for which they reported Voigt moduli K = 291 GPa and G = 88 GPa, whereas our ML models predicted values K = 276 GPa and G = 203 GPa; the G values are not comparable.…”
Section: Resultssupporting
confidence: 61%